Numerical Investigation of Stress Block for High Strength Concrete Columns - Nizar Assi; Husain Al-Gahtani; Mohammed A. Al-Osta (Salehan Institute of Higher Education, 2020)
This paper is intended to investigate the stress block for high strength concrete (HSC) using the finite element model (FEM) and analytical approach. New stress block parameters were proposed for HSC including the stress intensity factor (α1) and the depth factor (β1) based on basic equilibrium equations. A (3D) finite element modeling was developed for the columns made of HSC using the comprehensive code ABAQUS. The proposed stress parameters were validated against the experimental data found in the literature and FEM. Thereafter, the proposed stress block for HSC was used to generate interaction diagrams of rectangular and circular columns subjected to compression and uniaxial bending. The effects of the stress block parameters of HSC on the interaction diagrams were demonstrated. The results showed that a good agreement is obtained between the failure loads using the finite element model and the analytical approach using the proposed parameters, as well as the achievement of a close agreement with experimental observation. It is concluded that the use of proposed parameters resulted in a more conservative estimation of the failure load of columns. The effect of the stress depth factor is considered to be minor compared with the effect of the intensity factor.